MEDIA KOMUNITAS SUPORTER SEPAKBOLA SEBAGAI OPINION LEADER DI MEDIA SOSIAL: (Studi Etnografi Virtual dan Analisis Isi pada Media Sosial Twitter Komunitas Suporter Persib, Viking Persib Club, Viking Frontline, dan Simamaung) - Nurdiantara, Robby Rachman; Rabathy, Qisthy; Komala, Elly; Rizqullah, Annisa Fitri; Rizqullah, Fairuz Rasendriya (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2024)
This study focuses on how supporter community media become opinion leaders on Twitter. The objective is to analyze the social media activities of Persib Bandung's supporter community media on Twitter as opinion leaders; to describe the interaction and communication patterns that occur; to identify, analyze, and understand the role of Persib Bandung's supporter community media as opinion leaders on Twitter; and to analyze how these media shape and influence public opinion among Persib supporters using Twitter. A qualitative approach, utilizing virtual ethnography and content analysis, was employed to collect data through observing the virtual community on Twitter. The findings reveal that Viking Persib Club, Viking Frontline, and Simamaung play significant roles in shaping opinions among Bobotoh, Persib supporters. Viking Persib Club engages in direct interaction, information dissemination, and organizes various activities and campaigns that strengthen community solidarity. Viking Frontline stands out with its deep criticism of club-related issues, while Simamaung provides news, information, and in-depth analysis of club performance and policies. The interaction and communication patterns between the community media and their followers demonstrate that social media functions not only as a communication tool but also as a platform for building relationships, solidarity, and supporter identity. Supporters actively participate in discussions about various aspects of the club, not only responding to shared content but also regularly expressing their views. Furthermore, the supporter community media act as opinion leaders on Twitter, successfully shaping and influencing public opinion among supporters. Simamaung, in particular, not only provides information but also builds opinions and influences the actions of Persib supporters through its Twitter activities. The process of shaping public opinion on Twitter occurs through active roles in information dissemination, social action mobilization, and meaningful discussions about issues related to Persib Bandung. This research is expected to provide insights for community media managers and relevant stakeholders on effective communication strategies to influence and manage public opinion on digital platforms. Additionally, this study contributes to a deeper understanding of the dynamics of interaction and communication among football supporter communities in the digital era. Keywords: Bobotoh Persib, Digital Era, Social Media Twitter, Football Supporter Community Media, Opinion Leaders.